THE RESEARCH OF VOLUME OF SECONDARY RAW MATERIAL RESOURCES BY PRODUCTION OF FRUIT AND BERRY JUICE - Olga Yakovlevna Kolman; Galina Valentinovna Ivanova; Alexander Alexandrovich Mashanov (Современная наука и инновации, 2022)
The Article is devoted to the study of the volume of secondary raw materials in the production of fruit juices depending on the methods of obtaining juices and raw materials (fresh berries, ice cream), methods and modes of storage of raw materials and to study the impact of these factors on the percentage of juice yield, i.e. on the volume of waste. For the food industry, sources of dietary fiber in vegetable raw materials are divided into traditional (cereals, vegetables, fruits, berries) and non-traditional sources of raw materials (herbs, algae, wood, etc.). One of the non-traditional types of raw materials can serve as secondary raw materials-in particular waste of food and processing industry of agriculture. This can be, in particular, berry pomace, which is formed in the production of juices, jams, jam, etc. Therefore, studies aimed at studying the juice yield of berries and determining the volume of secondary raw materials in the production of fruit juices, seem relevant. The purpose of the work is to determine the volume of secondary raw materials in the production of fruit juices, depending on the methods of obtaining juices and raw materials (fresh berries, ice cream), methods and modes of storage of raw materials and to study the impact of these factors on the percentage of juice yield, i.e. the volume of waste.